PID Controller of Sprayer Chassis by Sliding Mode - Hua Zhang (Journal of Control Science and Engineering)
In order to solve the straight line drive coordinated control problem of the four-wheel independent drive sprayer chassis, the dynamic model of sprayer chassis and electromagnetic proportional valve controlled hydraulic motor model are established. The additional yaw moment is designed to rectify the deviation with sliding mode variable structure control. PID control strategy is used to calculate the control voltage adjustment of the electromagnetic proportional valve. The simulation results show that the accumulative deviation of the chassis is 0.2 m out of 100 m when the coordinated control strategy is adopted on different adhesive coefficient pavement, which is much smaller than the value without control. The test results of test prototype show that the yaw acceleration of the chassis can be as low as −0.0132 m/s2 on different adhesive coefficient pavement with coordinated control, which is smaller than the value without control, and the straight line drive requirements are met. It is feasible to combine sliding mode variable structure with PID control and use the electromagnetic proportional control technology in the straight line drive coordinated control of sprayer chassis by adding the yaw moment to rectify the deviation of chassis based on the yaw acceleration detection.